Legends about 5G Technology: The Truth - Oduroye, Ayorinde P,; Timothy Olaniran, Oyelowo,; Jerry Abayomi, Sarumi, (Scientific Research, New Technologies and Applications Vol. 7, 2024)
5G has come to stay. Since its rollout in 2019, 5G wireless networks have been growing in both availability and use cases. Apple was the first company to introduce 5G in 2020 by offering its newest iPhone with 5G compatibility. From there, the floodgates opened, and today as much as 62% of smartphones are built with 5G connectivity [1]. It has been noted that 5G networks transmit data as fast as 10 or even 20 gigabits per second (Gbps)—more than 100 times faster than 4G. The automotive, healthcare, logistics and manufacturing sectors are among the sectors projected to benefit the most from 5G capabilities. 5G has been hailed as a disruptive technology, comparable to artificial intelligence (AI), machine learning (ML) and the Internet of Things (IoT) in terms of the kinds of change it is bringing about. 5G has been praised for its transformative potential across a number of industries because it has the ability to move large volumes of data swiftly and securely between connected devices at speeds never achieved before [2]. Some of the most important differences between 5G and its predecessors are: firstly, “Smaller physical footprint”, that is 5G transmitters are smaller than those on predecessors’ networks, secondly, “Improved error rates”, meaning 5G’s adaptive Modulation and Coding Scheme (MCS) - a schematic for transmitting data, is more powerful than the schemes used in 3G and 4G networks, thirdly, “Better bandwidth”, that is, 5G can support more devices at the same time by using more radio frequencies including low-band (less than 1 GHz), mid-band (1 GHz–6 GHz) and high-band (24 GHz–40 GHz), and fourthly,” Lower latency”, that is the time it takes data to travel from one location to another is better than on previous networks, making routine activities like downloading a file or working in the cloud much faster [2].